Variability along a latitudinal gradient in the chiasma frequency and morphological characters of Dichroplus pratensis (Orthoptera: Acrididae) - Bidau, Claudio Juan (2005)
The grasshopper Dichroplus pratensis Bruner is polymorphic and polytypic for a complex Robertsonian system. In this species, centric fusions induce changes in number and position of chiasmata, and thus potentially affect intrachromosomal genetic recombination and genetic variability. Males and females, from 23 populations covering most of the geographic range of the species and spanning 22 degrees of latitude, were studied. We analyzed chiasma frequency in relation to variability in six exomorphological characters. The chromosomal polymorphisms of D. pratensis are widely geographically distributed, and show a central-marginal pattern, in which the central populations (those occupying the ecologically optimal habitats) have high mean frequencies of different fusions per individual (F) of up to F = 3.00 and total chiasma frequencies as low as XT = 8.98 per cell, while those near the margins of the distribution (central Patagonia and the Andes) have very low levels of chromosomal polymorphisms [down to F = 0.00 in most geographically marginal locations), monomorphic karyotypes and high chiasma frequencies (XT = 11.66, in the southernmost (Rada Tilly, 45°57´S) and XT = 12.01 in the northernmost population (Volcán, 23°55´S)]. Increasing chiasma frequencies towards the margins of the range are positively and significantly correlated with increasing levels of morphological variability. The decrease in fusion polymorphism and the consequent increase in genetic recombination (both inter- and intrachromosomal) in the marginal areas, is a result of natural selection favouring higher levels of variability, which could be adaptive in ecologically harsher and changing environments